Flower / Pauline Georgina Priya Hebert Sundram - Hebert Sundram, Pauline Georgina Priya (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.